Mother's Experience in Caring for Premature Infants - Padila, Padila; Andrianto, Muhammad Bagus; Andri, Juli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explore the experiences of mothers in caring for premature babies who have been treated in the intensive care unit. This type of research is qualitative research with a phenomenological approach. The results showed that the knowledge of mothers about premature babies was on average the same, from definition to treatment, support received, and coping mechanisms. In conclusion, the results of interviews with informants obtained 6 (six) themes, namely the description of premature babies and their characteristics, causes of premature birth, the ability of mothers to care for premature babies, forms of maternal support, mother's self-coping while caring for premature babies and mother's reactions while caring for premature babies. Keywords: Experience, Mothers, Premature Babies.